The high-Reynolds-number stratified wake of a slender body and its comparison with a bluff-body wake. (25th February 2023) - Ortiz-Tarin, Jose L.; Nidhan, Sheel; Sarkar, Sutanu
Abstract: Abstract : The high-Reynolds-number stratified wake of a slender body is studied using a high-resolution hybrid simulation. The wake generator is a 6 : 1 prolate spheroid with a tripped boundary layer, the diameter-based body Reynolds number is Re= U_∞ D/ν = 10^5, and the body Froude numbers are Fr=U_∞ /ND={2, 10, ∞ } . The wake defect velocity decays following three stages with different wake decay rates (Spedding, J. Fluid Mech., vol. 337, 1997, pp. 283–301) as for a bluff body. However, the transition points among stages do not follow the expected Nt = Nx/U_∞ values. Comparison with the wake of a circular disk in similar conditions (Chongsiripinyo & Sarkar, J. Fluid Mech., vol. 885, 2020) quantifies the influence of the wake generator – bluff versus slender – in stratified flow. The strongly stratified Fr=2 wake is in a resonant state. The steady lee waves strongly modulate the mean flow, and relative to the disk, the 6 : 1 spheroid (a high-aspect-ratio shape) wake at Fr=2 shows an earlier transition from the non-equilibrium (NEQ) stage to the quasi-two-dimensional (Q2D) stage. The NEQ–Q2D transition is followed by a sharp increase in the turbulent kinetic energy and horizontal wake meanders. At Fr=10, the start of the NEQ stage is delayed for the spheroid. Transfers between kinetic energy and potential energy reservoirs (both mean and turbulence) are analysed, and the flows are compared in phase space (with local Froude and Reynolds numbers as coordinates). Overall, the results of this study point to the difficulty of finding a universal framework for stratified wake evolution, independent of the features of the body, and provide insights into how buoyancy effects depend on the wake generator.